2023
DOI: 10.1097/gox.0000000000005158
|View full text |Cite
|
Sign up to set email alerts
|

Role of Infrared Thermography in Planning and Monitoring of Head and Neck Microvascular Flap Reconstruction

Sravan Kumar Chava,
Mansi Agrawal,
Konduru Vidya
et al.

Abstract: Background: Reconstruction using microvascular free flaps has become the standard of care in head and neck cancer surgery, and their success lies in appropriate planning, adequate revascularization, and early detection of flap compromise so that prompt salvage is possible. This study evaluates the role of infrared thermography in the planning, execution, and postoperative monitoring of microvascular flaps in head and neck reconstructions. Methods: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…With IRT statistically significant difference was found in mean ∆T between viable and compromised flap. Chava 13 et al reported range of temperature difference of 0.1 to 1.8°C (mean 1°C) in viable flaps, while compromised flaps showed temperature from 2.4 to 5.4°C. Pappilon 14 et al reported temperature difference of 1.5°C in viable flaps and 3.7°C in compromised flaps in a study of 47 free flaps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With IRT statistically significant difference was found in mean ∆T between viable and compromised flap. Chava 13 et al reported range of temperature difference of 0.1 to 1.8°C (mean 1°C) in viable flaps, while compromised flaps showed temperature from 2.4 to 5.4°C. Pappilon 14 et al reported temperature difference of 1.5°C in viable flaps and 3.7°C in compromised flaps in a study of 47 free flaps.…”
Section: Discussionmentioning
confidence: 99%
“…23 Taking temperature difference (ΔT) rather than absolute value minimizes these influences. 11,13 Thermal sensitivity of the imaging device is another concern, more with the lowresolution thermal devices. 24 Initially IRT devices were cumbersome, nonportable, and costly but smartphone-based thermal camera is promising in accessibility and cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%